Lipopolysaccharide Induces Disseminated Endothelial Apoptosis Requiring Ceramide Generation - Adriana Haimovitz–Friedman; Carlos Cordón-Cardo; Shariff Bayoumy; Mark Garzotto; Maureen McLoughlin; Ruth Gallily; Carl K. Edwards; Edward H. Schuchman; Zvi Fuks; Richard Kolesnick (1997)
The endotoxic shock syndrome is characterized by systemic inflammation, multiple organ damage, circulatory collapse and death. Systemic release of tumor necrosis factor (TNF)-α and other cytokines purportedly mediates this process. However, the primary tissue target remains unidentified. The present studies provide evidence that endotoxic shock results from disseminated endothelial apoptosis. Injection of lipopolysaccharide (LPS), and its putative effector TNF-α, into C57BL/6 mice induced apoptosis in endothelium of intestine, lung, fat and thymus after 6 h, preceding nonendothelial tissue damage. LPS or TNF-α injection was followed within 1 h by tissue generation of the pro-apoptotic lipid ceramide. TNF-binding protein, which protects against LPS-induced death, blocked LPS-induced ceramide generation and endothelial apoptosis, suggesting systemic TNF is required for both responses. Acid sphingomyelinase knockout mice displayed a normal increase in serum TNF-α in response to LPS, yet were protected against endothelial apoptosis and animal death, defining a role for ceramide in mediating the endotoxic response. Furthermore, intravenous injection of basic fibroblast growth factor, which acts as an intravascular survival factor for endothelial cells, blocked LPS-induced ceramide elevation, endothelial apoptosis and animal death, but did not affect LPS-induced elevation of serum TNF-α. These investigations demonstrate that LPS induces a disseminated form of endothelial apoptosis, mediated sequentially by TNF and ceramide generation, and suggest that this cascade is mandatory for evolution of the endotoxic syndrome.